Key Opinion Leaders (KOL) in Social Media as a Promotional Strategy - Angraini, Nadia (Universitas Negeri Makassar, 2025)
The Key Opinion Leader (KOL) strategy is currently a widely used strategy in marketing on social media platforms. KOL marketing itself usually uses public figures as intermediaries in communicating a product that aims to influence the desired audience. KOLs themselves are part of influencers on social media, it's just that KOLs are more specific in approaching the audience than influencers on social media. The purpose of this study is to find out whether it is true that influencers and KOL are interconnected with each other or vice versa. In addition, I as a researcher also want to know the role of KOLs and the effectiveness of using KOLs as a marketing strategy on social media. The data collection methods applied to this study include, namely, by identifying, evaluating, interpreting and searching for literature from various reliable sources such as reviewing journals related to the methods used in both local, national and international journals. In the search for articles that study marketing strategies and key opinion leaders (KOLs) on social media platforms, the search conducted by the researcher starts from peer review journal articles, publishers, conference proceedings and other works related to the study topic. The search was carried out using the Publish or Perish application to access the Google scholar database with the keywords Key opinion Leader, KOL, Strategy and social media, in the last 3 years from 2021 to 2023. The results show that influencers and KOLs have a relationship with each other. In addition, it is also known that marketing strategies on social media using KOLs are very effective. The effective role of KOLs can not only influence, but also change the behavior of the audience, KOLs influence a wide audience about the behavior and messages they distribute.